PESAN PENDIDIKAN MULTIKULTURAL DALAM SHOLAWAT SYAIKHONA KHOLIL - Ulil Izzah; Ahmad Marzuki (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2023)
The work of Indonesian Ulama is a prayer created by Indonesian Ulama with the aim of glorifying the Prophet Muhammad and also as a form of love. However, in these prayers, it is not uncommon for Ulama to also insert various other prayers which are also related to multicultural education messages. This research uses library research methods (Library Research). Regarding the primary sources that the author uses are books related to Sholawat Nusantara such as one of the books by Ahmad Zainuddin M.Th.I, while the secondary sources come from books, articles, magazines or other sources of information related to the problem being studied. The results of this research are that in Syaikhona Kholil's prayers there is a message of multicultural education, namely regarding the essence of multicultural education.